2018
DOI: 10.2341/17-169-c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnification on the Precision of Tooth Preparation in Dentistry

Abstract: Magnification devices improved the precision of tooth preparation under simulated clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…In the previous study, magnifications were extensively discussed in endodontics and periodontics. 23,24 In restorative dentistry, few studies have addressed the effect of magnifications, they discussed the magnification effect on iatrogenic damage to the adjacent tooth surface, 25 geometrical shapes, 26 and ergonomic benefits. 27 No single study was found that discussed the effect of magnifications in total occlusal convergence for crown-prepared teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, magnifications were extensively discussed in endodontics and periodontics. 23,24 In restorative dentistry, few studies have addressed the effect of magnifications, they discussed the magnification effect on iatrogenic damage to the adjacent tooth surface, 25 geometrical shapes, 26 and ergonomic benefits. 27 No single study was found that discussed the effect of magnifications in total occlusal convergence for crown-prepared teeth.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Recent studies with objective visual tests in a simulated clinical setting showed a large variability in the near visual performance of dentists (independent of their age) and a significant deficiency due to presbyopia from above 40 years of age. Over the last several decades, magnifying aids such as loupes and microscopes have also become an important tool in dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, magnifying aids such as loupes and microscopes have also become an important tool in dentistry. 8 What is true for dentists is also essential for dental hygienists because their daily work consists not only of probing periodontal pockets or root surfaces but also of the visual detection of carious lesions, filling fractures and calculus. [1][2][3][4][5][6][7][8] Recent studies with objective visual tests in a simulated clinical setting showed a large variability in the near visual performance of dentists (independent of their age) and a significant deficiency due to presbyopia from above 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations